Science Learning Achievement of Class IV Students at State Elementary School 2 Segeran - Wilsa, Asrizal Wahdan; Rasilah, Rasilah; Salam, Melly Alaihis (Journal of General Education and Humanities, 2024)
This study aims to improve learning achievement by enhancing the Problem-solving learning model in science lessons on plant material in class IV students at State Elementary School 2 Segeran, Juntinyuat District, Indramayu Regency. This is a Class Action Research (CAR) conducted in 2 cycles. The research subjects were 29 Class IV students at State Elementary School 2 Segeran, Juntinyuat District, Indramayu Regency. Research data was obtained through tests, observations, and documentation. Data analysis used a qualitative descriptive analysis technique. The study results showed an increase in the learning achievement of Class IV students at State Elementary School 2 Segeran, Juntinyuat District, Indramayu Regency through the Problem-solving learning model. Improvement in learning achievement is indicated by an increase in the average percentage of aspects of student learning outcomes from 41% in pre-cycle to 51% in cycle I, then increased to 82% in cycle II. Based on these results, it can be concluded that there is an increase in student learning achievement in learning through the application of the Problem-solving learning model in the Natural Sciences subject matter Plants in class IV students at State Elementary School 2 Segeran, Juntinyuat District, Indramayu Regency